Pricing Variance Swaps Under Stochastic Volatility with an Ornstein-Uhlenbeck Process - Jia, Zhaoli; Bi, Xiuchun; Zhang, Shuguang (Journal of systems science and complexity, 2015)
Pricing variance swaps under stochastic volatility has been an important subject pursued recently. Various approaches have been proposed, mainly due to the substantially increased trading activities of volatility-related derivatives in the past few years. In this note, the authors develop analytical method for pricing variance swaps under stochastic volatility with an Ornstein-Uhlenbeck（OU） process. By using Fourier transform algorithm, a closed-form solution for pricing variance swaps with stochastic volatility is obtained, and to give a comparison of fair strike value based on the discrete model, continuous model, and the Monte Carlo simulations.